2014
DOI: 10.1097/meg.0000000000000158
|View full text |Cite
|
Sign up to set email alerts
|

Higher free serum cortisol is associated with worse survival in acute variceal bleeding because of cirrhosis

Abstract: Higher FC is present in cirrhosis with AVB compared with CC and is associated independently with bleeding-related mortality. However, whether high FC solely indicates the severity of illness or whether there is significant adrenal insufficiency cannot be discerned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 53 publications
2
9
1
1
Order By: Relevance
“…Tsai et al found that the mean serum total cortisol level was 16.8 µg/dL for the whole group of patients. This value is consistent with cortisol levels of 24.3 µg/dL obtained by others in patients with cirrhosis and variceal hemorrhage or 16.8 µg/dL in critically ill patients without cirrhosis . Moreover, serum total cortisol levels measured by Tsai et al were well above those measured by others in patients with stable cirrhosis (11.6 µg/dL) or 11.9 µg/dL in healthy subjects .…”
Section: Commentsupporting
confidence: 90%
See 4 more Smart Citations
“…Tsai et al found that the mean serum total cortisol level was 16.8 µg/dL for the whole group of patients. This value is consistent with cortisol levels of 24.3 µg/dL obtained by others in patients with cirrhosis and variceal hemorrhage or 16.8 µg/dL in critically ill patients without cirrhosis . Moreover, serum total cortisol levels measured by Tsai et al were well above those measured by others in patients with stable cirrhosis (11.6 µg/dL) or 11.9 µg/dL in healthy subjects .…”
Section: Commentsupporting
confidence: 90%
“…This value is consistent with cortisol levels of 24.3 µg/dL obtained by others in patients with cirrhosis and variceal hemorrhage or 16.8 µg/dL in critically ill patients without cirrhosis . Moreover, serum total cortisol levels measured by Tsai et al were well above those measured by others in patients with stable cirrhosis (11.6 µg/dL) or 11.9 µg/dL in healthy subjects . Together these findings suggest that, like critically ill patients without cirrhosis, patients with cirrhosis and variceal hemorrhage have basal hypercortisolemia.…”
Section: Commentsupporting
confidence: 89%
See 3 more Smart Citations